Importance of consent in the research - Manandhar, Dr. Naresh; Joshi, Prof. Sunil Kumar (International Journal of Occupational Safety and Health, 2020)
Research involving human participants needs to be scientifically valid and should be conducted according to accepted ethical standards. Research ethics provides guidelines for responsible conduct of research on human participants. It primarily protects the human participants of research and also educates and monitors researchers conducting health research to ensure a high quality of ethical standard. Consent is a research process of information exchange between the researcher and the human participants of research. Information provided to the human participants of research should be adequate, clearly understood by the participant of research with decision-making capacity and the research participant should voluntarily decide to participate. Respect for persons requires that the participants of research should be allowed to make choices about whether to participate or not in the research.